The Influence of the PjBL Learning Model with Google Sites Media on Student Learning Outcomes of Pencak Silat in Class X SMAN 1 Driyorejo - Widad, Sofwul; Bambang Ferianto Tjahyo Kuntjoro (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The purpose of this research was to determine whether or not there was an influence of the PjBL learning model with Google sites media and how much percentage influence it had on student learning outcomes in class X SMAN 1 Driyorejo. This type of research is a pre-experimental design with a quantitative approach using a one group pretest-posttest design. The population in this study were all class X students of SMAN 1 Driyorejo. The sample in this study used the cluster random sampling technique. After being generalized, 1 class was randomly selected and class X-6 was selected as the sample in this study. This research was carried out in 4 meetings with written test instruments and performance tests, with data analysis using the t-test obtaining a significance value of 0.00 or less than 0.05, it can be said that there is an influence of the PjBL model with google sites media, then to measure the size of the effect using the N-gain formula gets a percentage of 68.47% or is quite effective, so it can be concluded that the PjBL model with google sites media for class X student learning outcomes of SMAN 1 Driyorejo is quite effective.